FORMULASI DAN EVALUASI FISIK SEDIAAN SHOOTING EKSTRAK BUNGA KARAMUNTING (Melastoma malabathricum L.) - Citrariana, Shesanthi; Febrianto, Yahya; Rahman, Sudarman; Fatiqin, Awalul; Suprayogi, Thatit; Alfanaar, Rokiy; Arsana, Mu’afa Purwa (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Soothing gel is a new cosmetic preparation in society with physical properties that increase the acceptability and effectiveness of therapy. Karamunting (Melastoma malabatricum L.) is a plant that is widely known in the Central Kalimantan region. Karamunting flowers contain flavonoid, alkaloid and saponin. The flavonoid in karamunting can be used as antioxidants. The aim of this research is to formulate karamunting flower extract (Melastoma malabathricum L.) as a soothing gel and evaluate the physical properties. The formulation method used variations of carbopol and HPMC with an extract concentration of 5%. Phytochemical testing of the extract was carried out using a tube test and total flavonoid using UV-Vis. The physical properties of the gel were tested in the form of organoleptic, homogeneity, viscosity and adhesion tests. The total flavonoid yield of karamunting flower extract was 21.22% w/w. Organoleptic properties: odorless aroma, brownish red color, and cool sensation on the skin. The preparation is homogeneous and has a viscosity of 200-300 dpa's and an adhesive force of 10.50-21.24 seconds. So it can be concluded that shooting gel karamunting flower extract has good physical properties.